Conocimientos, actitudes y prácticas asociados al estado nutricional en niños de 1 a 3 años del CDI San Juan de Llullundongo y Cochapamba periodo octubre 2023 – febrero 2024. - Carvajal Pasto, Ligia Elena (2024)
In the communities of San Juan de Llullundongo and Cochapamba, the existence of significant nutritional problems in the child population has been identified. The (CDI) "Learning Together" in Cochapamba and "Pachamama" in San Juan de Llullundongo, have become study focuses to address these problems. Objective: Determine knowledge, attitudes and practices associated with nutritional status in children from 1 to 3 years of age at CDI San Juan de Llullundongo and Cochapamba. Methodology: descriptive, qualitative-quantitative, field, population of 49 children from CDI Cochapamba and San Juan de Llullundongo. The instrument used to collect information was a previously validated survey of knowledge, attitudes, eating practices and nutritional assessment. For the analysis of the information, the statistical software SPSS and Who Antro Plus were used, as, Results: with respect to knowledge about the consumption of sausages, 59.3% consider that it is necessary for the child to consume these foods. Regarding nutritional status, 14.3% present a normal range (Length/height for age), 79.6% of children present acute malnutrition for their age (P/E), 63.3% of children They have a normal BMI for age (BMI/E), 65% have moderate acute malnutrition with respect to Upper Arm Perimeter; identifying more than 50% of children with nutritional problems, within this we have alterations such as acute, severe malnutrition, overweight and emaciation. Conclusion: the identification of knowledge, attitudes and eating practices was carried out, where the majority of parents/guardians have erroneous knowledge about the theme used in the study Keywords: KNOWLEDGE, ATTITUDE, FEEDING PRACTICE, NUTRITIONAL STATUS